Onychomadesis sebagai Komplikasi Langka pada Penyakit Tangan, Kaki, dan Mulut: Laporan Kasus: Laporan Kasus - Suwarni, Riana; Nuryanto, Anjar (PT Kalbe Farma Tbk., 2026)
Introduction: Onychomadesis is a rare nail disorder characterized by the separation of the nail plate from the nail matrix, which may result in nail shedding. It has been reported as a late complication of hand, foot, and mouth disease (HFMD), a common viral infection in childrenthat is usually self-limited but may present with various complications. Case: A 4-year-old boy had developed whitish transverse lines on his fingernails and toenails, followed by separation of the nail from the nail matrix. Two months prior to the nail changes, the patient experiencedfever accompanied by papulovesicular rashes around the mouth, hands, and feet, as well as aphthous lesions in the oral cavity consistent with HFMD infection. At the time of the nail involvement, there was no pain, inflammation, or signs of secondary infection. Discussion: Based on the clinical history and physical findings, a diagnosis of onychomadesis as a late complication of HFMD was established. Onychomadesis is known to occur weeks to months after HFMD and is generally self-limited without the need for specific therapy. Conclusion: Onychomadesismay occur as a late complication of HFMD in children. The condition is benign, does not require special treatment, and is expected to resolve completely within 6 weeks.